Alignment of European Regulatory and Health Technology Assessments: A Review of Licensed Products for Alzheimer's Disease - Dekker, Marieke J. H. J.; Bouvy, Jacoline C.; O'Rourke, Diana; Thompson, Robin; Makady, Amr; Jonsson, Pall; Gispen-de Wied, Christine C. (Frontiers in Medicine, 2019)
Aims: To facilitate regulatory learning, we evaluated similarities and differences in evidence requirements between regulatory and health technology assessment (HTA) bodies of Alzheimer’s disease (AD) approved products. Methods: The European marketing authorisation application dossiers and European public assessment reports (EPARs) of the licensed AD drugs were screened to identify the phase III randomised controlled trials (RCTs) and outcomes used. We also screened the assessment reports of the National Institute of Health and Care Excellence (NICE, England) and the National Health Care Institute (ZiN, the Netherlands) to identify the studies and outcomes used in HTA assessments. Results: The applications dossiers of donepezil, galantamine, rivastigmine, and memantine contained 16 phase III RCTs in total. These trials were also included in HTA assessments except that NICE excluded studies that were not published (n=2) or trials that included patients with other types of dementia (n=3). In the regulatory assessments the focus was on cognitive and global outcomes, and to some extent on function. In the HTA assessment of the clinical effectiveness other domains were also covered including: function, behaviour and mood, and, occasionally, quality of life. In the economic analyses of NICE the domains cognition, function, and quality of life were included. Conclusion: There was a large overlap in inclusion of trials in regulatory and HTA assessments, although the focus on specific outcomes slightly differed. Understanding the methods and perceptions of both authorities can stimulate regulatory and HTA cross-talk and further alignment, and therefore more rapid patient access to new treatments.